2020
DOI: 10.3390/ma13051144
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Metal-Composite Friction Spot Joints under Environmental Conditions

Abstract: The current paper investigates the durability of the single-lap shear aluminum-composite friction spot joints and their behavior under harsh accelerated aging as well as natural weathering conditions. Four aluminum surface pre-treatments were selected to be performed on the joints based on previous investigations; these were sandblasting (SB), conversion coating (CC), phosphoric acid anodizing (PAA), and PAA with a subsequent application of primer (PAA-P). Most of the pre-treated specimens retained approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Main characteristics are mentioned as viscosity of polymer, cooling rate and aluminium surface structure that may prevent full interface wetting, including insufficient sealing against the environment. 47 Pre-treatment with phosphoric acid anodizing and subsequent application of primer enabled the best performance in ultimate lap shear strength (ULSS) after one year of natural aging (more than 80% of initial ULSS). More than doubled reduction in global mechanical static performance were reported for samples that were pre-treated by conversion coating and sandblasting, reaching 57% and 59% respectively of the initial ULSS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Main characteristics are mentioned as viscosity of polymer, cooling rate and aluminium surface structure that may prevent full interface wetting, including insufficient sealing against the environment. 47 Pre-treatment with phosphoric acid anodizing and subsequent application of primer enabled the best performance in ultimate lap shear strength (ULSS) after one year of natural aging (more than 80% of initial ULSS). More than doubled reduction in global mechanical static performance were reported for samples that were pre-treated by conversion coating and sandblasting, reaching 57% and 59% respectively of the initial ULSS.…”
Section: Resultsmentioning
confidence: 99%
“…45,46 Besides the polymeric film, also the surface pretreatment has a relevant influence on the joint aging behavior. Goushegir et al 47 concluded that during accelerated aging of FSpJ joints the complete wetting of aluminium surface with molten polymer hinders the moisture diffusion into the joint interface. Main characteristics are mentioned as viscosity of polymer, cooling rate and aluminium surface structure that may prevent full interface wetting, including insufficient sealing against the environment.…”
Section: Effect Of Pps Interlayermentioning
confidence: 99%
“…On the other hand, in the resin-to-metal FSSW process, frictional heat generated between the tool and the metal is used to heat the thermoplastic resin to its melting point. Some studies [10][11][12][13] have been conducted to apply FSSW to CFRTP-to-metal welding since heat and pressure can be applied simultaneously in a short time. Conventional equipment used for joining metallic materials can also be converted for this use.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, the PMH was generally fabricated with traditional bonding, but the poor bonding strength, high cost, and complicated procedures inevitably limit its application. [ 8–12 ]…”
Section: Introductionmentioning
confidence: 99%